The relationship between dynamic stability and functional movementperformance ability in team sport and martial arts young male athletes - Pedak, K.; Bazaniov, B.; Rannama, I. (Journal of Human Sport & Exercise, 2018)
Introduction. The aim of this study was to compare the functional movement performance ability and Dynamic postural stability of athletes from team sport (basketball, handball, volleyball) and martial arts (judo, taekwondo, karate). Methods. 45 team sport (age =16,27 ± 1,7 years; height=183,2± 6,6 cm and BMI=23,5 ± 3,8) and 19 martial arts athletes (17,6±2,2a years; height=177,6±6,7cm and BMI=24,4±3,7). Participants were screened using the 100-point scale FMSTM protocol. Counter-movement jump test DPSI was measured by Kistler force plates. All statistical analysis was computed using the IBM SPSS Statistics (version 23.0). Results. The mean composite FMS 100-point scale was 55,1±9,3 and team sports athletes 45,0±6,4. Martial arts athletes shows statistically significantly higher score in active straight-leg raise 4,4±3,1 vs 7,9±3,9 (p<0,05) and trunk stability push-up test 4,4±3,5 vs 7,1±4,5 (p<0,001). There was not statistically significant difference between other five tests. There was moderate correlation between seven different FMS exercises scores and DPSI values of martial arts atheletes (r= 0,51) and team sports athletes (r=0,47).Conclusion. The results of the study indicate low FMS score in both groups. The team sport athletes have more problems with muscles of the hamstring and trunk muscles stabilizing than martial artists. Relationship between dynamic balance abilty and atheltis performance is less clear.